2021
DOI: 10.1177/14733250211024734
|View full text |Cite
|
Sign up to set email alerts
|

Emotional intelligence as a part of critical reflection in social work practice and research

Abstract: Social workers often experience higher levels of burnout compared with other healthcare professionals. The capacity to manage one’s own emotional reactions efficiently, frequently in complex care settings, is central to the role of social workers. This article highlights the complexity of emotions in social work research and practice by exploring the perspective of emotional intelligence. The article is both theoretical and empirical, based on reflections from a qualitative longitudinal study interviewing fath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…The result of this study validates social cognitive theories ( Bandura 1986 ) and supports previous findings that individual personality traits are significantly associated with creative self-efficacy ( Fino and Sun 2022 ; Karwowski and Lebuda 2016 ). Emotional intelligence, as an individual’s trait to interact emotionally with others, profoundly affects an individual’s perception and integration of the external environment ( Herland 2022 ). Previous studies have shown that emotional intelligence has a significant predictive effect on interpersonal relationships.…”
Section: Discussionmentioning
confidence: 99%
“…The result of this study validates social cognitive theories ( Bandura 1986 ) and supports previous findings that individual personality traits are significantly associated with creative self-efficacy ( Fino and Sun 2022 ; Karwowski and Lebuda 2016 ). Emotional intelligence, as an individual’s trait to interact emotionally with others, profoundly affects an individual’s perception and integration of the external environment ( Herland 2022 ). Previous studies have shown that emotional intelligence has a significant predictive effect on interpersonal relationships.…”
Section: Discussionmentioning
confidence: 99%
“…The examples of crisis interactions analysed in this article have shown how the security context in which the pedagogues act can influence the work of project employees and create situations in which excessive demands are placed on them unwillingly through diffuse feelings of being threatened and latent fears, especially when security questions and dangers are taboo or it remains unclear whether a client is in fact prone to violence or is merely labelled as 'radical'. This reveals the fact that their work includes 'emotional labour' (Hochschild, 1983, p. 7), excluding negative feelings or emotional dissonance, suppressing feelings or -in other situations -using them in a targeted way (Haugstvedt and Gunnarsdottir, 2021;Herland, 2021;Moesby-Jensen and Nielsen, 2015). The basis for this could be a conscious and targeted engagement with one's own emotions, as well as the emotional dynamics within the relationship to and communication with the clients.…”
Section: Discussion and Implications For Practicementioning
confidence: 99%
“…In addition, I also tried to identify my own feelings and in what way these affected me as a researcher. As the participants' stories were re‐told by me and thus inherently co‐constructed, this necessitated that I pay specific attention to my own subjectivity in the re‐telling, to examine the ways in which ‘the author's meanings’ may be at work in the new narrative (Herland, 2021; Herland, 2022). I therefore examined my own position in a reflexive manner, looking into my own emotional responses.…”
Section: Methodsmentioning
confidence: 99%